1992
DOI: 10.5694/j.1326-5377.1992.tb121509.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Nocardia species in Queensland: A review of 102 clinical isolates

Abstract: Objective To review the species distribution, pathologic significance and disease associations of clinical isolates of Nocardia and related bacteria in Queensland, and to examine the characteristics, treatment and outcome of patients infected with these organisms. Design and setting A retrospective review of Queensland State Health Laboratory records provided microbiological data for Nocardia isolates referred from other laboratories during the period January 1983 to December 1988. Clinical information was ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
81
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 26 publications
6
81
1
Order By: Relevance
“…Our study accords with previous reports of high mortality (31%–40%) and high rates of ICU admission in unrestricted studies of pulmonary and disseminated nocardiosis [10, 19, 26–28]. Severe disease was common, and fulminant presentations were seen in both immunocompetent and immunocompromised individuals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study accords with previous reports of high mortality (31%–40%) and high rates of ICU admission in unrestricted studies of pulmonary and disseminated nocardiosis [10, 19, 26–28]. Severe disease was common, and fulminant presentations were seen in both immunocompetent and immunocompromised individuals.…”
Section: Discussionsupporting
confidence: 92%
“…In 13% of cases (8 of 61), hazardous alcohol use was the only reported predisposing factor for nocardiosis. These findings support previous studies that have suggested (1) an association between hazardous alcohol use and nocardiosis [19, 21–23], (2) that alcohol abuse may be a predisposing factor for dissemination of Nocardia to the CNS [21, 22, 24], and (3) that alcohol may be an important cofactor in predisposition to Nocardia infection due to its effect on macrophage function [25]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[5,3234] A previous study of nocardiosis in Queensland was published in 1992 and included 102 isolates from a range of clinical sites. [35] Of these, 45 isolates were classified as N asteroides . Given that this publication predates the routine use of molecular diagnostics, it is likely that a different range of species would be identified should the same isolates be tested today.…”
Section: Discussionmentioning
confidence: 99%